Visible Light Mediated Organophotoredox-Catalyzed One-Pot Domino Synthesis of Novel 6,7 Disubstituted 1H-Pyrroles - Govindaraju, Santhosh; Tabassum, Sumaiya (Topics in catalysis, 2025)
The development of environmentally benign protocols to synthesize novel N -heterocycles is vital in the field of synthetic organic chemistry. We herein report a successful one-pot domino synthesis of novel 6,7 disubstituted 1 H -pyrroles using substituted phenacyl bromide, barbituric acid/Meldrums acid, aromatic amines catalysed by 5 mol% Fluorescein in presence of visible light. This procedure is a useful and adaptable method for the synthesis of pyrroles since it is compatible with a wide range of sensitive functional groups, does not require column chromatography purification. During the reaction, Fluorescein may catalyse the formation of enamine leading to amino alcohol which subsequently undergoes dehydration to give 6,7 disubstituted 1 H -pyrroles. All the synthesized derivatives were obtained in 90–95% yields and were characterized by 1 H, 13 C NMR and HRMS (ESI) analysis. Graphical Abstract